2009
DOI: 10.1136/adc.2008.147884
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in selecting an appropriate neonatal thyroid stimulating hormone (TSH) screening threshold

Abstract: A reduced threshold of 6 mU/l will increase the number of false positive term infants by 126%, but abnormalities of thyroid function requiring treatment will be detected. We suspect that the additional expense involved in setting a lower threshold is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 18 publications
2
56
1
11
Order By: Relevance
“…Nevertheless, some recently reported data suggest that the incidence of CH has progressively increased in the past two decades both in the United States and Europe [1,2,3,4,5,6,7]. This substantial increase in cases almost doubling previous estimates has been discussed in the neonatal screening community, and several factors have been implicated.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, some recently reported data suggest that the incidence of CH has progressively increased in the past two decades both in the United States and Europe [1,2,3,4,5,6,7]. This substantial increase in cases almost doubling previous estimates has been discussed in the neonatal screening community, and several factors have been implicated.…”
Section: Introductionmentioning
confidence: 75%
“…In recent years, several screening programs have lowered the TSH cutoff (CO) used, finding more affected children but increasing the recalled population [4,5,6]. This approach, however, raises questions on the benefits and objectives of screening strategies and underscores the importance of accurate diagnostic confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a borderline cut-off point will increase the detection of CH [11,12] and will inevitably pick up less severe cases. There is no evidence of where the lower cut-off point should sit and the UKNSPC value of 10 mU/l has been set by expert personal opinion with no subsequent evidence to support or refute this standard.…”
Section: Resultsmentioning
confidence: 99%
“…Korada and cols., 2010, decreased the limit for the TSH cutoff from 20 µU/mL to 6 µU/mL and observed that, in 67 children with TSH between 6.1 and 10 µU/mL, 4 continued to display TSH levels greater than 6 µU/mL (23). In the Brazilian state of Santa Catarina, the recommended cutoff point is 6 µU/mL because, at 10 µU/mL, some CH cases can be missed (20).…”
Section: Discussionmentioning
confidence: 99%